Perlindungan Hukum Terhadap Tenaga Kerja Perempuan Berdasarkan Undang-Undang Nomor 13 tahun 2003 tentang Ketenagakerjaan - Kanyaka Prajnaparamita (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Social policies designed to protect female workers that worked at night and promote equality in the workplace have a controversial effect on labor market outcomes. Restrictions on working hours and pregnancy benefits stipulated in applicable laws help protect the responsibilities of women workers who work at night for their families and ensure their physical security, but this regulation can raise doubts about the safety of women working at night. Protection of female workers has been regulated in the Law Number 13 of 2003 concerning Manpower and Decree of the Minister of Manpower and Transmigration Article 76. In addition, the regulation is also regulated in the Transmigration of the Republic of Indonesia No. Kep 224 / Men / 2003 regulates the obligations of employers who employ female workers or laborers, where the application process is carried out directly by the employer through a work agreement between employers and workers which is then supervised by the authorized agency. Keywords: Legal Protection, Women, Working at Night Abstrak Kebijakan sosial yang dirancang untuk melindungi pekerja perempuan yang bekerja di malam hari dan mempromosikan kesetaraan di tempat kerja memiliki efek kontroversial pada hasil pasar kerja. Pembatasan jam kerja dan tunjangan kehamilan yang diatur dalam undang-undang yang berlaku membantu melindungi tanggung jawab pekerja perempuan yang bekerja di malam hari terhadap keluarganya dan memastikan keamanan fisik mereka, tetapi peraturan ini dapat menimbulkan keraguan terhadap keamanan perempuan yang bekerja pada malam hari. Perlindungan terhadap tenagakerja perempuan telah diatur dalam undang-undang yakni Undang-Undang Nomor 13 tahun 2003 tentang Ketenagakerjaan dan Keputusan Menteri Tenaga Kerja Pasal 76. Selain itu, pengaturannya diatur juga dalam Transmigrasi RI No.Kep 224/Men/2003 mengatur kewajiban pengusaha yang memperkerjakan pekerja atau buruh perempuan, dimana proses penerapanya dilakukan langsung oleh pengusaha lewat perjanjian kerja antara pengusaha dengan tenaga kerja yang kemudian diawasi oleh instansi yang berwenang. Kata Kunci : Perlindungan Hukum, Perempuan, Bekerja di Malam Hari